2022
DOI: 10.15376/biores.18.1.1215-1231
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon and cellulose-reinforced biodegradable chitosan foams

Abstract: Chitosan foams with promising mechanical properties, heat-insulating ability, and flame retardancy were produced through oven drying. The chitosan foams were reinforced with cellulose, boric acid, and different ratios of activated carbon. The foams showed desirable low density (80.2 to 109.8 kg/m3) and compression properties. The compression resistance and compression modulus of foams ranged between 53.6 and 98.5 KPa and 214 to 394 KPa, respectively. Thermal conductivity tests revealed that the foams endowed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
11
0
4
Order By: Relevance
“…Removing the solvent in the suspension also causes the xanthan gum and cellulose fibers to intertwine. It is known that this has a significant effect on the density increase of the produced foam material [ 51 ]. Xanthan gum has the most significant effect on the density value of the produced foam material.…”
Section: Resultsmentioning
confidence: 99%
“…Removing the solvent in the suspension also causes the xanthan gum and cellulose fibers to intertwine. It is known that this has a significant effect on the density increase of the produced foam material [ 51 ]. Xanthan gum has the most significant effect on the density value of the produced foam material.…”
Section: Resultsmentioning
confidence: 99%
“…There were many studies in which the mechanical properties of materials produced with the addition of zinc borate at high rates were adversely affected. 18,39 Previous studies indicated that the concentration of chitosan and its molecular weight have a positive effect on the mechanical properties of chitosan-based materials. For example, increasing the concentration of chitosan from 0.5% to 3% in chitosan films gave rise to an increase in their mechanical properties, 40 and an increase in the concentration of chitosan from 1% to 5% resulted in higher mechanical strength of chitosan hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Cellulose and chitosan have made them popular biopolymers to manufacture and/or reinforce otherwise weak materials, including foams. 17,18 These two biopolymers utilize in many industries, such as paper, pharmaceutics, food, water treatment,, biomedical treatment, agriculture, cosmetics, and textiles. 19 Cellulose is crystalline, strong, and rigid.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that when activated carbon used in different matrices and with various materials, enhances its mechanical properties, 61 while excessive amounts of activated carbon and other type fillers added to the mixture tend to diminish these mechanical characteristics. 62,63 In a rubber related study, it was reported that adding activated carbon produced by the physical activation method to the SBR matrix up to 20%-30% improves the mechanical properties, however, due to the formation of clustering in the rubber matrix with the addition of activated carbon over 30%, the interaction of the rubber filler and the mechanical properties decreased. 64 In another study, activated carbon produced by physical activation method from dry Tecoma leaves was added to standard Malaysian rubber.…”
Section: Breaking Strength (Tensile Strength) and Unit Elongation Exp...mentioning
confidence: 99%